ANALISIS PENATAAN PEMUKIMAN DI SENTANI KABUPATEN JAYAPURA - Lembang, Nataniel; Rante, Harmonis; Rusim, Dewi Ana (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2023)
The handling of slum settlements has been mandated through Presidential Regulation No. 18 of 2020 concerning the 2020-2024 National Medium Term Plan Development Plan (RPJMN). Sentani City as the center of government in Jayapura Regency also needs to make arrangements for existing slum settlements. This was followed up through the Decree of the Regent of Jayapura Regency No. 188.4/332 of 2020 concerning Determination of the Location of Slum Housing and Slum Settlement in Jayapura Regency in 2020. This study aims to identify and analyze the condition of slum settlements in Jayapura Regency and develop strategies and handling them. Primary data collection was done through direct observation, documentation and field interviews. Secondary data through coordination with related parties, information through the media and related research journals. Data analysis was carried out qualitatively. The results showed that there were 49.09% of houses that were uninhabitable, only 10.38% of drinking water was provided for households, there were 3,655 households that had not been served by electricity, still high house construction and construction without environmental impact analysis and building permit regulations, unavailability of public cemeteries owned by local governments, high cases of land grabbing and blocking, many environmental roads are in a damaged condition, inadequate drainage in residential areas, there are still many lands and lands that have not been certified and land management has not been optimal. The strategy and handling of slum settlements in Jayapura Regency is referring to the Jayapura Regency's 2017-2022 medium-term development vision, potential area of Jayapura Regency, the problem of the uneven distribution pattern of infrastructure and facilities in the Jayapura Regency area and the prospect of developing new residential areas..